Pretransplant HOMA-β Is Predictive of Insulin Independence in 7 Patients With Chronic Pancreatitis Undergoing Islet Autotransplantation. Issue 10 (16th September 2022) - Beamish, Christine A.; Gaber, A. Osama; Fraga, Daniel W.; Hamilton, Dale J.; Sabek, Omaima M.
Abstract : Background: Islet and β-cell function is intrinsic to glucose homeostasis. Pancreatectomy and islet autotransplantation (PIAT) for chronic pancreatitis (CP) treatment is a useful model for assessing islet function in the absence of immune-suppression and to perform extensive presurgical metabolic evaluations not possible from deceased donors. We recently showed that in CP-PIAT patients, preoperative islet identity loss presented with postoperative glycemic loss. Here, we examine presurgical islet function using Homeostatic Model Assessment-Beta Cell Function (%) (HOMA-β) and glycemic variables and compared them with postsurgical insulin independence and their predicted alignment with Secretory Unit of Islet Transplant Objects (SUITO) and beta cell score after transplantation (BETA-2) scores. Methods: Seven CP-PIAT patients were assessed for β-cell function metrics, including pretransplant and 6-mo posttransplant HOMA-β using insulin and C-peptide and evaluations of proposed insulin independence by SUITO and BETA-2 graft function equations. These were compared with oral glucose tolerance tests and pancreas histological samples taken at the time of transplant, examined for β-cell maturity markers. Results: Pre-PIAT, HOMA-β (60%−100%) associated with post-PIAT insulin independence. This association was only moderately supported by post-PIAT SUITO threshold scores (≥26) but robustly by BETA-2 scores (≥16.2). Appropriate posttransplant oral glucose tolerance test curves were found in those patients with normal pretransplant HOMA-β values. Preoperative low serological β-cell function was displayed by concurrent evidence of β-cell identity alterations including colocalization of insulin and glucagon, loss of urocortin-3, and increased intra-islet vimentin in patients who were insulin-dependent post-PIAT. Conclusions: These data encourage HOMA-β assessment before PIAT for estimating posttransplant insulin independence.